Phylogeny of Ameronothroidea in the south polar region and the phylogeography of selected species on sub-antarctic Marion Island - Mortimer, Elizabeth (Stellenbosch : Stellenbosch University, 2012)
Thesis (DPhil)--University of Stellenbosch, 2008.